Barriers and facilitators for health professionals referring Aboriginal and Torres Strait Islander tobacco smokers to the Quitline. (18th October 2017) - Martin, Kimberley; Dono, Joanne; Rigney, Nathan; Rayner, Joanne; Sparrow, Alana; Miller, Caroline; Mckivett, Andrea; O'Dea, Kerin; Roder, David; Bowden, Jacqueline
Abstract: Objective: To examine the barriers and facilitators among health professionals to providing referrals to Quitline for Aboriginal and Torres Strait Islander clients who smoke. Methods: A brief online survey, based on the Theoretical Domains Framework, was completed by 34 health professionals who work with Aboriginal and Torres Strait Islander people in South Australia and the Northern Territory. Results: Respondents who frequently made referrals had higher domain scores than less frequent referrers for 'Skills and knowledge' (M=4.44 SD=0.39 vs. M=4.09 SD=0.47, p <0.05) and 'beliefs about capabilities' (M=4.33 SD=0.44 vs. M=3.88 SD=0.42, p <0.01). Barriers to providing referrals to Quitline were lack of client access to a phone, cost of a phone call, preference for face‐to‐face interventions, and low client motivation to quit. Conclusions: Health professionals working with Aboriginal and Torres Strait Islander clients should be supported to build their skills and confidence to provide referrals to Quitline and other brief cessation interventions. Building capacity for face‐to‐face support locally would be beneficial where phone support is not preferable. Implications for public health: Engaging with health professionals who work with Aboriginal and Torres Strait Islander people to increase referrals to Quitline is strategic as it builds on their existing capacity to provide cessation support.